A comparative evaluation of root canal area increase using three different nickel-titanium rotary systems: An ex vivo cone-beam computed tomographic analysis - Adrija Deka; AC Bhuyan; Darpana Bhuyan (Wolters Kluwer Medknow Publications, 2015)
Background and Objectives: The present study was undertaken to compare and evaluate the area increase of root canals with ProTaper, iRaCe and Revo-S systems using cone beam computed tomography for analysis. Materials and Methodology: Forty five extracted human mandibular premolars having single canal and straight root were collected. Teeth were randomly assigned to three groups (n=15). Samples were decoronized by maintaining root length at 14 mm. Pre-instrumentation cone beam computed tomography scan was done after stabilizing the samples on wax blocks. The working length was determined at 1 mm short from the apical foramen by using a ISO 15 K-file tip protruding at apical foramen. Preparation was carried out according to the manufacturer's instructions. Finally, canals were instrumented upto 30/.06 apically for each group. After each instrumentation, root canals were irrigated with 2ml of 3% sodium hypochlorite solution followed by 2 ml of 17% EDTA solution. Final irrigation was done with 5ml of saline. Post instrumentation cone beam computed tomography scans of all samples in the 3 groups were acquired. Results: Mean percentage of area increase in different thirds of the canal was highest for ProTaper followed by i-RaCe and Revo-s system which was statistically significant. Interpretation and Conclusion: Root canal area increase was highest for ProTaper followed by i-Race and Revo-S systems.